Public Acceptance of Digital Library Services in Boyolali Regency - Nugroho, Rino A.; Pratiwi, Hanijaya Intan; Prakoso, Septyanto Galan; Rahmawati, Anisa Dwi (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
In 2017, Boyolali Regency ranked the lowest in Central Java Province regarding of E-Government development. The Boyolali Government has initiated several electronic-based service innovations, including the iBoyolali digital library service. This study aims to identify the factors influencing user acceptance of the iBoyolali application. This study employs the Unified Model of Electronic Government Adoption (UMEGA) framework and utilizes convenience sampling, collecting data through online questionnaires from 103 iBoyolali users. The data analysis used Partial Least Square - Structural Equation Modeling (PLS-SEM). The findings reveal that the digital library services in Boyolali Regency incorporate and practice the variables outlined in the UMEGA framework. Further analysis indicates that public acceptance of the iBoyolali service is generally positive. Specifically, the study identifies four UMEGA variables—performance expectation, effort expectation, social influence, and attitudes. Conversely, facilitating conditions and perceived risk did not significantly impact the acceptance of the iBoyolali service. This study provides important insights for the Boyolali Government and other stakeholders aiming to enhance the adoption of digital library services, offering a basis for developing strategies to improve user engagement and satisfaction.